전신 움직임을 요구하는 컨트롤러가 가상현실 디바이스에서 시지각과 가상현실 멀미에 끼치는 영향 - 김성호(Sung-ho Kim); 신동희(Dong-Hee Shin) (디지털콘텐츠학회논문지, 2017)
가상현실 경험에서 높은 감각적 몰입으로 시각으로 지각되는 정보와 전정기관, 체성감각 등 감각기가 지각하는 정보 간에 불일치가 생기면서 가상현실 멀미가 일어나 기기의 보급에 장애가 되고 있다. 본 연구는 기존의 감각의 충돌 이론에 착안하여 모션 컨트롤러로 대표되는 새로운 전반적인 신체의 움직임이 각성 정도와 현존감에 영향을 끼치며, 가상현실 멀미를 촉발할 수 있고 각성 정도는 감각적 몰입, 현존감과 깊은 관계가 있다는 가설을 세우고 실험을 통해 검증하였다. 특히 컨트롤을 위한 전체적인 신체의 움직임에 집중하여, 몸-머리 움직임과 대조하여 연구하였다. 실험의 결과로 신체 움직임과 각성 정도 간에 유의한 상관관계를 확인할 수 있었고, 현존감에 대해서도 일정 정도 유의한 상관 관계가 있음을 확인할 수 있었다. 또, 신체의 움직임이 있을 때, 안경의 착용 유무가 관측되는 가상현실 멀미에 중재변수로 역할을 하는 것을 확인할 수 있었다. Though new body movement based input system immerged in Virtual Reality (VR), VR still has a visually induced motion sickness (VIMS) problem to be accepted for users. VIMS are caused by changes in visually perceived movement that discord with vestibular system’s sense of movement. Not only Head-body movements, but also hand gestures to make commands and torso movement can affect visual movement perception by enhancing immersion and its psychological product; presence. The question arises does whole body movement and hand gesture to make commands are more dominant to arousal, presence, and VIMS? To address this question, we conducted “2 (IV1; head-body movements only vs. whole body movements) * 1” between subject design experiment. The results showed that significant effect on whole body movements and arousal, marginally significant effect on presence. Eyewear usage was a moderator between hand gesture and presence relationship. KCI Citation Count: 9